Corvids in Urban Environments: A Systematic Global Literature Review - Isma Benmazouz (MDPI AG, 2021)
Urbanization is one of the most prevalent drivers of biodiversity loss, yet few taxonomic groups are remarkably successful at adapting to urban environments. We systematically surveyed the global literature on the effects of urbanization on species of family Corvidae (crows, choughs, jackdaws, jays, magpies, nutcrackers, ravens, rooks, treepies) to assess the occurrence of corvids in urban environments and the factors affecting their success. We found a total of 424 primary research articles, and the number of articles has increased exponentially since the 1970s. Most studies were carried out in cities of Europe and North America (45.5% and 31.4%, respectively) and were directed on a single species (75.2). We found that 30 corvid species (23% of 133 total) regularly occur in urban environments. The majority (72%) of the studies reported positive effects of urbanization on corvids, with 85% of studies detecting population increases and 64% of studies detecting higher breeding success with urbanization. Of the factors proposed to explain corvids’ success (availability of nesting sites and food sources, low predation and persecution), food availability coupled with diet shifts emerged as the most important factors promoting Corvidae to live in urban settings. The breeding of corvids in urban environments was further associated with earlier nesting, similar or larger clutches, lower hatching but higher fledging success, reduced home range size and limited territoriality, increased tolerance towards humans and increasing frequency of conflicts with humans. Despite geographic and taxonomic biases in our literature sample, our review indicates that corvids show both flexibility in resource use and behavioral plasticity that enable them to exploit novel resources for nesting and feeding. Corvids can thus be urban exploiters of the large-scale modifications of ecosystems caused by urbanization.